The Effect Of Earning Assets Quality And Non-Performing Loans To The Profitability In The Rural Banks (BPR) Of Medan Municipality In 2014-2016 - Laelis Neni; Lily Karlina Nasution; Mayang Murni (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
Every credit disbursed by a bank always has a risk. This credit will directly impact to the value of the impaved credit itself. The high level of bad debts meant the deterioration of the quality of earning assets (QEA) in the banking system subsequently leads to a decline in the ability of banks to make profits. The purpose of this study was to search the influence of QEA and impaired debts on profitability in the rural banks, either partially or simultaneously. This study used financial data of nine rural banks (BPR) in Medan Municipality during the period 2014-2016. The data analyzed by using classical assumptions and multiple regression tests while the data processing used SPSS tools. The results of this research were that partially for QEA and non-performing loans (NPL) did not affect ROA profitability and simultaneously the quality of earning assets and NPL impaired debts did not affect the profitability of ROA with a value of f equal to 0 594 with Sig 0 563 0 05 Keywords: Earning Asset Quality, Non-Performing Loans, Profitability